2016
DOI: 10.1371/journal.pone.0164712
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Method for Separating and Enriching Nano and Submicron Particles from Titanium Dioxide Found in Food and Pharmaceutical Products

Abstract: Recent studies indicate the presence of nano-scale titanium dioxide (TiO2) as an additive in human foodstuffs, but a practical protocol to isolate and separate nano-fractions from soluble foodstuffs as a source of material remains elusive. As such, we developed a method for separating the nano and submicron fractions found in commercial-grade TiO2 (E171) and E171 extracted from soluble foodstuffs and pharmaceutical products (e.g., chewing gum, pain reliever, and allergy medicine). Primary particle analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…The application of E171 in food was subjected to a (re-)evaluation by the European Food Safety Authority (EFSA) in 2016 [4] and was re-approved for use in food. It is commonly applied in confectionery (including candies, chewing gum, glazings) but was demonstrated also in pastries, low-fat dairy products, and sauces [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of E171 in food was subjected to a (re-)evaluation by the European Food Safety Authority (EFSA) in 2016 [4] and was re-approved for use in food. It is commonly applied in confectionery (including candies, chewing gum, glazings) but was demonstrated also in pastries, low-fat dairy products, and sauces [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the EFSA opinion, several studies characterized commercially available pristine E171 materials and food products containing E171 [6,7,9,42,43,52,[56][57][58]. In general, mean particle sizes between 106 and 145 nm and size distributions ranging from 30 nm to 400 nm were reported for electron microscopy (EM) analyses [6,9,42,43,[56][57][58]. One study showed a size distribution ranging from 30 to 600 nm for scanning electron microscopy (SEM) and 20 to 400 nm for asymmetric flow field-flow fractionation coupled with inductively coupled plasma mass spectrometry (AF4-ICP-MS) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of aluminum-containing packaging, consumer products and kitchenware has increased 10 , as well as the use of chemical solvents, leaches and acids. Several metal species are present in a significant amount in food as nano-scaled particles [11][12] and migrate into food from packaging material [13][14][15] . Like other orally ingested metals, aluminum nanoparticles overcome the different compartments of the human digestion tract.…”
Section: Introductionmentioning
confidence: 99%
“…Food-grade titanium dioxide (TiO 2 ) labeled as E171 in the European Union has been consumed by humans for more than 50 years (Joint Food and Agriculture Organization of the United Nations and the World Health Organization in 2013) but the TiO 2 toxicity caused by inhalation has highlighted the attention regarding possible adverse effects by other routes of exposure, including oral intake. E171 is a food additive used for whitening and brightening in foodstuffs, dried vegetables, soups, vitamins, chocolates, snacks, chewing gums and solid candies (Kim et al, 2018;Peters et al, 2014;Rompelberg et al, 2016;Weir, Westerhoff, Fabricius, Hristovski, & von Goetz, 2012), generic and name-brand medicines (Faust, Doudrick, Yang, Capco, & Westerhoff, 2016), among others. E171 can be used at quantum satis in the European Union, which means that there is no established limit of E171 added to achieve the quality of the food product, while in the USA, the Food and Drug Administration (FDA) permits 1% E171 as maximum in the food (Lehto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%